Map of The Needs of UMSU Students on Al-Islam and Muhammadiyah Curriculum - Nurzannah Nurzannah; Mahmud Yunus Daulay; Nurman Ginting (Nazhruna: Jurnal Pendidikan Islam, 2021)
The purpose of this study was to produce a map of the needs of UMSU students for Al-Islam and Kemuhammadiyahan (AIK) courses. This type of research is qualitative research that uses survey techniques. Data collection was carried out by questionnaires and interviews. The data analysis techniques used are; describe the data, analyze, and interpret, and conclude. The results showed that the map of the needs of UMSU students for AIK courses were: 1) Students with religious understanding backgrounds other than Muhammadiyah (92 people/76.8%) of the 396 respondents stated that the provision of Worship courses, in particular, not through doctrine and coercion, but must pay attention to the background of the religious understanding they already profess. 2) Non-Muslim students generally state that Worship courses are not taught in the form of doctrine as given to Muslim students but must consider their religious background, and AIK courses should be taught in the form of Islamology courses, or the like. 3) Students from Muhammadiyah schools tend to want the provision of AIK courses to be packaged with other programs. Or by combining face-to-face in class with more interesting programs, not just face-to-face routines. 4) Most of the respondents stated that learning strategies and methods need to be adapted to the needs of students.